Exploring the factors influencing the adoption of smart farming technologies in agriculture - A bibliometric analysis literature review - Poorna, Teja K; Senthilkumar, M; Manimekalai, R; Saravanan, P A; Vanitha, G (Plant Science Today, 2025)
Smart Farming Technologies (SFTs) play a crucial role in enhancing agricultural productivity, sustainability and resource efficiency. However, a variety of technological, economic, social and policy-related issues influence their adoption. This study uses bibliometric analysis to highlight collaborative efforts in this field, uncover global research trends and investigate the major factors impacting the adoption of SFT. The study uses Visualization of Similarities (VOS) viewer and R studio to perform bibliographic coupling, keyword co-occurrence and citation network analysis using Scopus as the main database. The selection of excellent, peer-reviewed studies is guaranteed via a PRISMA-based methodology. The results show notable differences in adoption rates, with affluent countries making tremendous progress while underdeveloped regions struggle with digital literacy, inadequate infrastructure and budgetary restraints. High upfront expenditures, problems with interoperability, worries about data privacy and farmers' aversion to change are some of the main obstacles. Adoption rates are greatly impacted by social factors, institutional support and governmental regulations, underscoring the necessity of focused interventions. To close the gap between the development of technology and its practical application, the study emphasizes the value of collaborative research, interdisciplinary approaches and policy frameworks. To increase adoption, it is essential to address infrastructure and financial issues, improve farmer training and fortify policy measures. The findings deepen our understanding of the dynamics of smart farming adoption and provide evidence-based suggestions for industry executives, researchers and policymakers. To guarantee extensive SFT implementation and long-term agricultural resilience, future studies should concentrate on localized adoption models, sustainable financing and adaptable regulations.